Wskaźniki środowiskowe zrównoważonego rozwoju Unii Europejskiej - Graczyk, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article deals with strategic documents of EU related to sustainable development, as well as sixth Programme of workings on environment. The author also presents the indicatory systems of monitoring of sustainable development with special regard on environmental indicators.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 131-141